Pendugaan Jarak Genetik pada Itik Cihateup, Cirebon dan Mojosari - A Muzani; B Brahmantiyo; C Sumantri; A Tapyadi (Faculty of Animal Science, Bogor Agricultural University, 2005)
A study on morphological body conformation of Cihateup, Cirebon and Mojosari ducks was carried out to determine the genetic distance and discriminant variables. The research was done at PT Dwi Mitra Daq, Gunung Sindur, Bogor, using 30 Cihateup, 30 Cirebon and 30 Mojosari ducks, from September to November 2004. Length of neck, wing, circumference of chest, deep chest, body weight, circumference of tarsometatarsus, length of chest, third digit, tarsometatarsus, tibia, femur and maxilla were measured to observe their body sizes to determine the genetic distance and discriminant variables. Data obtained were analyzed by using GLM (General Linear Model) and simple discriminant analysis with SAS package program version 6.12 and program MEGA2 to make the construction of tree fenograms. Cihateup ducks had larger body size (i.e. length of neck, wing, circumference of chest, deep chest, length of third digit and femur) than Cirebon and Mojosari ducks, but were smaller on length of tarsometatarsus than Mojosari ducks. Results from canonical analysis showed that the most discriminant variables were obtained from the length of third digit tarsometatarsus, tibia and femur. Cihateup ducks were mixed with Cirebon ducks (36,67%), Cirebon ducks were mixed with Cihateup ducks (43,33%) and Mojosari ducks (3,33%), Mojosari ducks were mixed with Cihateup ducks (3,33%) and Cirebon ducks (13,33%). Mahalanobis genetic distance showed that Cihateup and Cirebon ducks had a genetic distance of 0,880, Cihateup and Mojosari, and, Cirebon and Mojosari had 1,786. Key words : duck, morphologycal, genetic distance, body conformation